Homozygosity for the APOE E4 Allele is Solely Associated with Lower Cognitive Performance in Brazilian Community-dwelling Older Adults – The Bambuí Study - Quintino-Santos, Sandra Regina; Lima-Costa, Maria Fernanda; Uchoa, Elizabeth; Firmo, Josélia Oliveira de Araujo; Moriguchi, Emílio Hideyuki; de Castro-Costa, Érico (Revista brasileira de psiquiatria, 2012)
Objective: To investigate if APOE E4 allelic status is associated with the cognitive functioning of elderly individuals. Methods: Participants (n = 1,408) from the Bambuí Cohort Study of Aging were selected based on the results from both variables (APOE genotype and MMSE score). Gender, age, education, marital status, skin color, GHQ score and biological measures were used as confounding factors for adjusting the logistic regression. Results: The population was in Hardy-Weinberg equilibrium, and the APOE E4 allele frequency was 13.4%. APOE E4 allele homozygosity conferred a superior odds ratio (OR) for cognitive impairment (OR = 3.1) compared to E4 allele heterozygosity (OR = 0.99) even when adjusted for age, sex, education, marital status, skin color, triglycerides, HDL, systolic pressure, and GHQ (OR = 2.9). No differences were observed between the other covariates. Conclusions: The APOE E4 allele was observed to have a dramatic effect on cognitive impairment, especially in homozygotes, which comprised approximately 2% of the population. Objetivo: Demonstrar que a presença do alelo APOE E4 está associada ao declínio cognitivo em idosos vivendo em comunidade. Método: Participaram do estudo 1408 residentes na cidade de Bambuí (MG) com 60 ou mais anos de idade. A variável dependente do estudo foi a função cognitiva, mensurada pelo Mini Exame do Estado Mental (MEEM). A variável de interesse do estudo foi o genótipo da apolipoproteína E (APOE). Para efeito de ajustamento na regressão logística foram consideradas como covariáveis o sexo, escolaridade, cor da pele, estado civil, sintomas depressivos, dosagem de triglicerídeos, HDL e pressão sistólica. Resultados: A frequência alélica do gene APOE (E4, E3, E2) mostrou distribuição em equilíbrio de Hardy-Weinberg. Foi detectada uma forte associação entre a presença do alelo E4 e o comprometimento cognitivo quando em homozigose (OR: 3,1; IC 95%: 1,39–6,99) mesmo após ajustamento por todas as potenciais variáveis de confusão (OR: 2,9; IC95%: 1,15–7,71). Conclusões: Os resultados mostraram que existe uma forte associação entre a presença do alelo E4da APOE e a função cognitiva em idosos. Esta associação existiu somente entre indivíduos homozigotos (E4E4), indicando dependência da dose gênica no comprometimento cognitivo.